CIAT Strategy 2014–2020. Building an eco-efficient future - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2014)
In pursuit of increased research impact, CIAT has developed a new strategy for the period 2014-2020. Reaffirming eco-efficiency as a guiding principle of our research, the strategy explains how the Center’s growing research team and networks will capitalize on past and current work to translate smarter use of resources into valuable impacts, such as higher incomes, improved child nutrition, and better water supplies. The new strategy responds to various trends shaping the world today, including population growth, rapid urbanization, extensive land degradation, climate change, and exciting scientific advances. The strategy also takes into account key developments in each of the regions where CIAT works – sub-Saharan Africa, Asia, and Latin America and the Caribbean. Additional documents include: Realizing the value of ecosystem services for human well-being; Tropical forages for eco-efficient livestock production; Reducing yield gaps for sustainable intensification of agriculture; and Sustainable food systems for a rapidly urbanizing world.